Sine-ry a cinematic, experiential landscape design for the Philippine National Railways within the City of Manila - Cabrera, Shanaia Kate J. (College of Architecture, University of the Philippines Diliman, 2019)
The Philippine National Railway (PNR) is a national legacy -- a transportation pioneer with rich, historical value that deserves high regard , maintenance or preservation, care, and optimum utilization (Licerio, 2008). However, every day, deterioration and defacement of our cultural and historical buildings take place. The defunct railway passing the Northern and Central Luzon from Manila has almost disappeared from both memory and physical structure. Maintaining, developing, and saving cultural and historical objects is a concern of cultural conservation. This could help transform our cultural objects into more lasting, visible reminders of the past and relevant inspiration for our present activities (Perdon, 1978). This study brings a cultural analysis of visual and sensory experiences of train mobility into landscape design; specifically, the Philippine National Railway within the boundaries of Manila. The mobile Travel Glance provides a visual "cinematic" experience of moving landscape images to the travelling spectator (Larsen, 2010). Since the study focuses mainly on the integration process of human and heritage conservation, and environmental psychology of space, it follows a step-by-step procedure carefully considering the site's existing features and conditions : Manila's cultural influence, and user-commuter benefits. This results to an experiential landscape linking stations in Manila that caters to the visual, railway experience and cultural appreciations of the masses.